Spatial modelling of the transport mode choice: application on the Vienna transport network - Šinko, Simona; Rupnik, Bojan; Prah, Klemen; Kramberger, Tomaž (Transport, 2021)
A new approach for spatial modelling of transport mode choice is presented in the paper. The approach tackles the problem by considering the trade-off between subjective and objective factors. To obtain mode Preference Rates (PRs) based on subjective factors, the Analytic Hierarchy Process (AHP) method is applied. The objective factors are expressed with the journey time from any point in the map to destination according to the available transport mode choice on the specific connection. The results are presented as PRs of individual transport modes. The model is validated on the conducted the survey, with students of Vienna University of Economics and Business (WU) as a target audience. Members of different target groups (age, national, employment) decide differently regarding the transport choice, so it is better to analyse them separately. The presented model can be used for the city transport planning in any urban area. It can help promote the sustainable modes of transport in the areas that are less adjusted in sustainable manner.